Ailinella mirabilis gen. n., sp. n. (eucestoda: pseudophyllidea) from Galaxias maculatus (Pisces: Galaxiidae) in the Andean-Patagonian region of Argentina - de Pertierra, Alicia A Gil; Semenas, Liliana G (Folia parasitologica, 2006)
Ailinella gen. n. (Pseudophyllidea: Triaenophoridae) is proposed to accommodate Ailinella mirabilis sp. n. from Galaxias maculatus (Jenyns, 1842), a freshwater fish inhabiting the Andean lakes in Argentinean Patagonia. Ailinella belongs to the Triaenophoridae because it has a marginal genital pore, a follicular vitelline gland, and a ventral uterine pore. The new genus can be distinguished from other triaenophorids by the following combination of characters: a small body size, a low number of proglottides, which are longer than wide, a truncated pyramidal to globular scolex, a rectangular apical disc, presence of the neck, lack of internal longitudinal musculature separating the cortex from the medulla, testes distributed in one central field surrounding the ovary laterally and posteriorly, the vagina predominantly anterior to the cirrus sac, vitelline follicles circum-medullary, the genital pores post-equatorial, a saccate uterus, and operculate eggs. Blade-like spiniform microtriches were present on all tegument surfaces, and tumuli on all surfaces of the scolex and the anterior surface of the neck. Microtriches were characterized according to their size and density, and tumuli according to their size, inter-tumulus distance and density. Ailinella mirabilis is the first cestode described from G. maculatus and the second triaenophorid species recorded from a South American freshwater fish.
Keywords: Osmeriformes; Argentina; Animals; Intestines; střeva; mikroskopie elektronová rastrovací; Female; zvířata; mužské pohlaví; Male; Cestoda; Microscopy, Electron, Scanning; ženské pohlaví